2022
DOI: 10.1155/2022/7739023
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Polyphenon 60 from Green Tea on Melanin and Tyrosinase in Zebrafish and A375 Human Melanoma Cells

Abstract: Polyphenon 60 (PP60) from green tea has long been used as an antioxidant, anticancer, antimicrobial, and antimutagenic. Aim of the Study. To investigate tyrosinase inhibition-related kinetic mechanism and antimelanogenesis potential of PP60. Materials and Methods. The effect of PP60 on melanin and tyrosinase was evaluated in A375 melanoma cells and zebrafish embryos. The melanoma cells were treated with 20, 40, and 60 µg/mL of PP60, and tyrosinase expression was induced by using L-DOPA. The western blot method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In turn, these compounds help improve cognitive processes such as memory [25]. The use of catechins has shown antioxidant effects both in cardiovascular and neurodegenerative diseases, and also in carcinogenic events, acting directly (removing ROS or chelating metal ions) or by indirect mechanisms, inducing the production of antioxidant enzymes or inhibiting prooxidants [26,27]. However, in relation to catechin and polyphenol-60, information is lacking related to their beneficial effects on non-pathological aging, which has been found, as in other polyphenol compounds, to be an important way of assessing their potential as antiaging molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these compounds help improve cognitive processes such as memory [25]. The use of catechins has shown antioxidant effects both in cardiovascular and neurodegenerative diseases, and also in carcinogenic events, acting directly (removing ROS or chelating metal ions) or by indirect mechanisms, inducing the production of antioxidant enzymes or inhibiting prooxidants [26,27]. However, in relation to catechin and polyphenol-60, information is lacking related to their beneficial effects on non-pathological aging, which has been found, as in other polyphenol compounds, to be an important way of assessing their potential as antiaging molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Among all bioactive compounds, phenolic compounds have been reported to have antioxidant, anti-carcinogenic, anti-microbial, anti-mutagenic and anti-inflammatory characteristics. 13,14 Previous studies have revealed the correlation between total phenolic content (TPC) and antioxidant capacity. 15 Synthetic antioxidants are expensive, possibly toxic, and more immunogenic than naturally occurring phenolics.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies describe almost every type of cancer that has been already tested in the ZF model, including BC [ 18 ], gastric cancer [ 19 ], colorectal cancer [ 20 ], non-small cell lung adenocarcinoma [ 21 ], pancreatic ductal adenocarcinoma [ 22 ], melanoma [ 23 ], glioblastoma [ 24 ], and others [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%